2015
DOI: 10.1186/s13000-015-0317-x
|View full text |Cite
|
Sign up to set email alerts
|

Combination of serum RASSF1A methylation and AFP is a promising non-invasive biomarker for HCC patient with chronic HBV infection

Abstract: BackgroundHypermethylation of the promoter region of the RAS association domain family 1A gene (RASSF1A) occurs widely in hepatocellular carcinoma (HCC) tissues. While the diagnostic performance of the use of RASSF1A methylation as a serum or plasma marker in patients with HCC has varied largely in the literature,we confirmed the clinical application value of serum RASSF1A methylation for HBV related HCC in this study.MethodsA total of 584 participants were recruited into this study, including 190 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 21 publications
1
35
0
1
Order By: Relevance
“…Although serum AFP level has been widely used for diagnosis of HCC, the sensitivity and specificity of AFP for HCC are limited (21). Therefore, it is urgent to identify novel potential biomarkers for early prognosis and monitoring of tumor recurrence, which is helpful for clinicians to select therapeutic strategies, so that the prognosis of HCC patients may be improved.…”
Section: Rhamm Mrna Clinical ----------------------------------------mentioning
confidence: 99%
“…Although serum AFP level has been widely used for diagnosis of HCC, the sensitivity and specificity of AFP for HCC are limited (21). Therefore, it is urgent to identify novel potential biomarkers for early prognosis and monitoring of tumor recurrence, which is helpful for clinicians to select therapeutic strategies, so that the prognosis of HCC patients may be improved.…”
Section: Rhamm Mrna Clinical ----------------------------------------mentioning
confidence: 99%
“…Apart from the selection of the detection technique and thresholds, the determination of the precise genomic positions of those CpG dinucleotides analyzed is also of great importance [82]. With regards to clinical heterogeneity, only 20.5% (9/44) of our enrolled articles mentioned the presence or absence of preoperative treatment [38,40,41,45,47,50,53,55]. Some studies suggested that both radiotherapy and chemotherapy can alter a patient's DNA methylation status; therefore, the type of preoperative treatment performed should be clari ed [83,84].…”
Section: Discussionmentioning
confidence: 99%
“… 38 , 39 But serum level of AFP was still frequently used for the diagnosis of HBV-relative HCC with considerable sensitivity and specificity in the People’s Republic of China. 40 In the meta-analysis of AFP and STAT4 expression, only three studies (including the current study) with 327 cases were included. 14 , 27 No relationship was found between AFP and STAT4 in the studies of Wubetu et al 14 and Wang et al 27 The relationship between STAT4 and AFP needs to be illuminated.…”
Section: Discussionmentioning
confidence: 99%